Luminescence Properties of Eu2+ and Mn2+ Doped Sr2MgSiO5 Phosphors - Pan Zhou; Dawei He; Yongsheng Wang; Haiteng Wang; Hongpeng Wu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Eu2+ions doped Sr2MgSiO5 phosphors, and Eu2+- Mn2+ions-doped Sr2MgSiO5 phosphors were prepared via high-temperature solid state reaction method and sol-gel process, respectively. Luminescent mechanism and characteristics of all samples were studied. The results showed that lattice structure of Eu2+ ion-doped Sr2MgSiO5 samples was pyramidal system. The influence of flux on luminescence properties of Eu2+ ion-doped Sr2MgSiO5 phosphor was studied. The results of spectral analysis showed that flux changed the emission intensity of Sr2MgSiO5: Eu2+ samples at different wavelengths. Emission wavelength and relative intensity of the samples changed. In order to study the luminescence properties and energy transfer between Eu2+ and Mn2+, Eu2+ ions and Mn2+ ions co-doped samples were prepared. The results showed that excitation bands of the samples ranged from 250nm to 450 nm. When excited at 365nm, the emission spectrum of the samples consisted of three bands: blue, green and red, respectively. When Eu2+ ions and Mn2+ ions co-doped, the energy of Eu2+ ions was transferred to Mn2+ ions, which made Mn2+ ions became luminescence center in Sr2MgSiO5host. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2642